CASE STUDY: PROBLEMS IN LEARNING MATHEMATICS (PHOBIA MATH, CHEATING, LOW MOTIVATION) - Septiani, Dwi Wulan; Cahyaningrum, Yuniana; Riera, Cin; Hidayah, Arinal (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
Based on the results of the study, learning problems are problems that are often experienced by students. Learning problems greatly affect the learning outcomes obtained by students. The problems experienced by students were more on learning skills. These problems must have the right handling, so that learning problems can be overcome. This research is a type of qualitative descriptive research. Because this research was conducted to describe or provide an overview of learning problems. Qualitative research is a study that intends to understand the phenomenon of what is experienced by research subjects, such as motivation, behavior, and actions. This research uses a case study method that can focus on a particular case to be analyzed carefully and thoroughly. In this study, the researcher collects a reference book or journal article. Based on these types of references, results will be generated related to the topic raised by the researcher. These references will be studied to get a detailed explanation of case studies of problems in learning mathematics, namely: phobia of mathematics, cheating and low motivation. The source of the data in this study were class VIII-C students of MTSN 10 Bireuen in the 2018/2019 academic year.